Antibodies Against Hypothalamus and Pituitary Gland in Childhood-Onset Brain Tumors and Pituitary Dysfunction - Patti, Giuseppa; Calandra, Erika; De Bellis, Annamaria; Gallizia, Annalisa; Crocco, Marco; Napoli, Flavia; Allegri, Anna Maria Elsa; Thiabat, Hanan F.; Bellastella, Giuseppe; Maiorino, Maria Ida; Garrè, Maria Luisa; Parodi, Stefano; et al. (Frontiers in Endocrinology, 2020)
Purpose: To detect the presence of Antipituitary (APA) and Antihypothalamus antibodies (AHA) in subjects treated for brain cancers, and to evaluate their potential association with pituitary dysfunction. Methods: We evaluated sixty-three patients with craniopharyngioma, glioma and germinoma treated with surgery and/or radiotherapy and/or chemotherapy at a median age of 13 years. Forty-one had multiple pituitary hormone deficiencies (MPHD), 6 had a single pituitary defect. GH was the most common defect (65.1%), followed by AVP (61.9%), TSH (57.1%), ACTH (49.2%) and gonadotropin (38.1%). APA and AHA were evaluated by simple indirect immunofluorescence method indirect immunofluorescence in patients and in fifty healthy controls. Results: Circulating APA and/or AHA were found in 31 subjects (49.2%) and in none of the healthy controls. In particular, 25 subjects out of 31 were APA (80.6%), 26 were AHA (83.90%) and 20 were both APA and AHA (64.5%). Nine patients APA and/or AHA have craniopharyngioma (29%), seven (22.6%) have glioma and 15 (48.4%) have germinoma. Patients with craniopharyngioma were positive for at least one antibody in 39.1% compared to 33.3% of patients with glioma and to 78.9 % of those with germinoma with an analogous distributions for APA and AHA between the three tumors. The presence of APA or AHA and of both APA and AHA was significantly increased in patients with germinoma. The presence of APA (P=0.001) and their titers (P=0.001) were significantly associated with the type of tumor in the following order: germinomas, craniopharingyomas and gliomas; an analogous distribution was observed for the presence of AHA (P=0.002) and their titers (P= 0.012). In addition, we found a significant association between radiotherapy and APA (P=0.03) Conclusions: Brain tumors especially germinoma are associated with the development of hypothalamic-pituitary antibodies and pituitary defects. The correct interpretation of APA /AHA antibodies in essential to avoid a misdiagnosis of an autoimmune infundibulo-neurohypophysitis or pituitary hypophysitis in patients with germinoma